Assessment of Li-Inventory in Cycled Si-Graphite Anodes Using LiFePO4 as a Diagnostic Cathode. Issue 10 (4th August 2018) - Dose, Wesley M.; Maroni, Victor A.; Piernas-Muñoz, Maria Jose; Trask, Stephen E.; Bloom, Ira; Johnson, Christopher S.
Abstract : An accounting of the lithium-inventory associated with Si-graphite composite anode cycling in a full cell is reported. The evaluation makes use of a Si-graphite/LiFePO4 diagnostic cell couple whereby Li supply is available from a capacity over-sized LiFePO4 cathode. Electrochemical results indicate that the irreversible capacity per cycle is progressive and cumulative, dependent on the lithiation capacity, but independent of Li-inventory. Under a capacity limited cycling protocol, however, capacity fade is delayed until the lithium reserve is consumed. Our analysis suggests a link between the total exchanged charge and the duration of the silicon particle degradation process, after which the Coulombic efficiency is improved. However, due to the large amounts of Li consumed in this long "formation" process, capitalizing on this could be difficult to achieve in practice. Results from Raman spectroscopy and scanning electron microscopy (SEM) of focused-ion beam (FIB) cross-sectioned samples indicate a dramatic increase to the Si-graphite electrode thickness and loss of Si domain microstructure after cycling, although the large voids present in the pristine electrode remain.